Tarfala meteorological data 1998 - Peter Jansson (Stockholm University, 2016)
This file set contains the complete registered meteorological data from
the "Tarfala met" AWS 1998. Included in the file set are the complete
set of data split into files for each parameter, the original logger
data, the Matlab program that takes the logger data and generates the
parameter files and finally the report summarizing the data and any
issues or changes made during the year.
Keywords: Atmospheric Sciences; 49999 Earth Sciences not elsewhere classified; Climate Science; 40105 Climatology (excl. Climate Change Processes); Climate Science; Klimatvetenskap; Other Earth Sciences; Annan geovetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap